Analysis of the utility of local content collections in the final assignment preparation process of undergraduate students at Diponegoro University - Adriyani, Elita; Christiani , Lydia (Berkala Ilmu Perpustakaan dan Informasi, 2025)
Introduction. Local content collections at Diponegoro University are widely utilized by final-year undergraduate students in preparing their final assignments. Although extensively accessed, the effectiveness of these collections remains underexplored. Accordingly, this research seeks to examine the relationship between the utilization of local content collections and the fulfillment of undergraduate students’ final assignment-related information needs. Research Methods. We used a quantitative correlational approach, by collecting data through questionnaires distributed to undergraduate students. Data analysis. The analysis was performed using descriptive and inferential statistical with SPSS version 26 software to verify the hypothesized relationships. Results and Discussion. We found that the correlation coefficient is 0.776, indicating a strong relationship between the utility of the local content collection and students’ information needs in compiling their final assignment. The p-value was 0.000, significant less than 0.05, indicating a significant and relevant connection between the two variables. Conclusion. The findings highlight the urgency of developing and managing local content collections in university libraries to support students’ academic success. This research recommends integrating these collections with the library information system to maximize access and utilization.